PENGARUH KNOWLEDGE SHARING, PENGALAMAN, DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT - Nur Shodiq; Bambang Suryono; Lilis Ardini (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
The purpose of this research is to conduct testing and find empirical evidence about the effect of knowledge sharing, experience and obedience pressure on audit judgment. The quantitative approach, namely the survey method, is the applied research approach. 50 Public Accounting Firms (KAP) in Surabaya and Sidoarjo are the total of the total population. To determine the number of samples from the population used purposive sampling method until later obtained a sample of 120 auditors. The Auditors of Public Accounting Firms (KAP) based in Surabaya and Sidoarjo are the respondents used in the ongoing research. In addition, multiple linear regression analysis is the analysis applied to the research. The results of this study prove empirically that knowledge sharing and experience have a positive influence on audit judgment. Obedience pressure has a negative relationship with audit judgment and does not empirically have a significant effect on audit judgment. The findings in this study indicate that the higher the pressure given to the auditor, the more inaccurate the judgments made by the auditor will be.